2017
DOI: 10.3390/nu9030192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia among Chinese Rural Residents

Abstract: This paper presents an analysis of the level of blood hemoglobin and the rates of anemia in Chinese rural residents in the 2010–2012 National Nutrition and Health Survey, and the change in its prevalence in rural residents during the last ten years. Our methodology included data from the Chinese Nutrition and Health Surveillance in 2010–2012, where samples were selected through the method of probability proportion to size. The study objects were from 150 sites in provinces, autonomous regions, or municipalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…In China, since rice is the main food, the iron deficiency is relatively high compared to many developed countries. China carried out its first national nutrition and health survey in 1959, which has subsequently been conducted every 10 years since 1982 (Li et al, ). The prevalence of anemia in different regions in China tends to be different.…”
Section: Iron Deficiency In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…In China, since rice is the main food, the iron deficiency is relatively high compared to many developed countries. China carried out its first national nutrition and health survey in 1959, which has subsequently been conducted every 10 years since 1982 (Li et al, ). The prevalence of anemia in different regions in China tends to be different.…”
Section: Iron Deficiency In Chinamentioning
confidence: 99%
“…Higher rates of anemia were observed in Central and Eastern China compared with Western China (Li, Luo, Medina, & Rozelle, ). Although women of reproductive age and the elderly still had a high prevalence of anemia, prevalence of anemia in the Chinese rural population was 9.7% in 2010–2012, which obviously decreased compared to the decade (Li et al, ).…”
Section: Iron Deficiency In Chinamentioning
confidence: 99%
“…0% during 20030% during to 20040% during and 20110% during to 20120% during (Le, 2016. Previous Studies reported that anemia in early childhood may contribute to irreversible body development, mainly in the brain and leads to increased mortality among infants and toddlers (Li et al, 2017). According to WHO women and young children, are the most vulnerable group, have shown moderate-to-severe anemia and indicates that over 20% of the population of most of the member countries is affected (De Benoist, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Complications of anemia are fatigue and congestive heart failure, severity frequency increases as the anemia progresses (Adamu et al, 2017) Anemia is growing rapidly and emerging as a threat even in the developed world, United States (US) represents a prevalence of 4.0-7.0% during 2003 to 2004 and 2011 to 2012 (Le, 2016). Previous Studies reported that anemia in early childhood may contribute to irreversible body development, mainly in the brain and leads to increased mortality among infants and toddlers (Li et al, 2017). According to WHO women and young children, are the most vulnerable group, have shown moderate-to-severe anemia and indicates that over 20% of the population of most of the member countries is affected (De Benoist, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%